2009
DOI: 10.1038/nature08144
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of G-protein-coupled receptors

Abstract: G-protein-coupled receptors (GPCRs) mediate most of our physiological responses to hormones, neurotransmitters and environmental stimulants, and so have great potential as therapeutic targets for a broad spectrum of diseases. They are also fascinating molecules from the perspective of membrane-protein structure and biology. Great progress has been made over the past three decades in understanding diverse GPCRs, from pharmacology to functional characterization in vivo. Recent high-resolution structural studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
1,766
1
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,100 publications
(1,806 citation statements)
references
References 67 publications
16
1,766
1
23
Order By: Relevance
“…As a model of GPCRs, Rho has been extensively studied, and since the first report of its crystal structure, several GPCRs structures have been solved by X-ray crystallography [1][2][3][4][5] . Rho is found in the rod outer segment (ROS) membranes of the photoreceptor cells of the retina where it is embedded in the lipid bilayer surrounded by ~65-70 phospholipids per protein molecule [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…As a model of GPCRs, Rho has been extensively studied, and since the first report of its crystal structure, several GPCRs structures have been solved by X-ray crystallography [1][2][3][4][5] . Rho is found in the rod outer segment (ROS) membranes of the photoreceptor cells of the retina where it is embedded in the lipid bilayer surrounded by ~65-70 phospholipids per protein molecule [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…An early discrimination of the investigated ligands into these categories in silico is of high importance for pharmaceutical research. Most GPCR crystal structures represent an inactive state which has been considered to be capable for the discovery of antagonists and inverse agonists only [12][13][14]. To date, only the structure of opsin [15] and most recently structural models of active conformations of the b 2 -adrenergic receptor (B2AR) [16][17][18], the agonist-bound b 1 -adrenergic receptor [19] and a constitutively active rhodopsin [20] could be potentially used as a template for the modelling of active GPCRs and subsequent virtual screening for agonists.…”
Section: Introductionmentioning
confidence: 99%
“…They all activate heterotrimeric G proteins upon agonist binding, but their seven helices exhibit significant divergence, reflecting a high degree of ligand variation, from small amines to peptide hormones 9, 10 . A recent study demonstrated that, despite such variation among GPCRs, some conserved features in terms of intramolecular atomic distances were discernible 11 .…”
Section: Introductionmentioning
confidence: 99%